Computational Approaches in microRNA Biology - Schmitz, Ulf; Gupta, Shailendra K.; Vera, Julio; Wolkenhauer, Olaf (Encyclopedia of Biomedical Engineering, Vol. 3, 2019)
MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression at the posttranscriptional level by binding to mRNA targets and inducing translational repression or target degradation via the RNA-induced silencing complex. Since miRNAs were first identified, computational approaches have played an important role for understanding their biosynthesis, modes of target regulation, and interplay with other mechanisms of gene regulation. In this essay we discuss computational methodologies used in miRNA biology research. More specifically, we introduce concepts for the prediction of miRNAs and their target genes: miRNA structure prediction and miRNA expression profiling approaches, coupled with the functional characterization of miRNAs. We then review approaches used for modeling miRNA-mediated gene regulatory networks.<br
CRIS-Team WoS Importer:2020-03-27
Keywords: Mathematical modeling of miRNA regulation; microRNA; microRNA databases and web resources; microRNA gene prediction; microRNA target hubs; microRNA target prediction; Regulatory networks; Target regulation